2023
DOI: 10.3389/fpls.2023.1102491
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphodynamics, evolution, and ecology of vertical roots

Abstract: The roots of some coastal and wetland trees grow peculiar vertical protrusions, the function of which remains unclear. Here, using computational simulations based on first-principles fluid and sedimentation dynamics, we argue that the protrusions work together to create an elevated patch of sediment downstream of the tree, thereby creating its own fertile flood-protected breeding grounds for the seedlings. In our simulations, we vary the vertical root diameter, root spacing and total root area and show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Hence, the presence of vegetation can be sought as it constitutes an integral component of sustainable river and estuarine ecosystems. The presence of vegetation in river systems and shoreline areas is widely acknowledged as a substantial and ever-changing element of the ecosystem (Heidelman & Vural, 2023;Turker et al, 2019). The experiment conducted by Holzenthal et al (2022) demonstrated the interplay among waves, sediment, and flexible vegetation.…”
mentioning
confidence: 99%
“…Hence, the presence of vegetation can be sought as it constitutes an integral component of sustainable river and estuarine ecosystems. The presence of vegetation in river systems and shoreline areas is widely acknowledged as a substantial and ever-changing element of the ecosystem (Heidelman & Vural, 2023;Turker et al, 2019). The experiment conducted by Holzenthal et al (2022) demonstrated the interplay among waves, sediment, and flexible vegetation.…”
mentioning
confidence: 99%